2021
DOI: 10.1186/s12944-020-01429-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid and triglycerides in Chinese children and adolescents with short stature

Abstract: Background Elevated triglyceride (TG) levels are a biomarker for cardiovascular disease (CVD) risk. The correlation between serum uric acid (SUA) and TG concentrations in adults or obese children is well established. However, studies on SUA and TG in children with short stature are limited. Aim To determine the relationship between SUA and TG levels in short children and adolescents. Method This was a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Many more sex- and age- lipoprotein associations are being discovered [ 5 , 14 , 15 , 16 ]: in the era of precision medicine, understanding how sex and age shape the lipidome can lead to better diagnosis and treatment of conditions that occur more frequently in one of the two sexes, present sex-specific symptoms and outcomes, or are characteristic of a specific age group [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many more sex- and age- lipoprotein associations are being discovered [ 5 , 14 , 15 , 16 ]: in the era of precision medicine, understanding how sex and age shape the lipidome can lead to better diagnosis and treatment of conditions that occur more frequently in one of the two sexes, present sex-specific symptoms and outcomes, or are characteristic of a specific age group [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, studies indicated that high TG could affect kidney function, thereby reducing renal excretion of SUA in the kidney and elevating SUA levels. 33,34 Also, decreased HDL was closely associated with elevated level of SUA. 35 Consequently, elevated AIP (elevated TG/decreased HDL) was positively related to HUA.…”
Section: Discussionmentioning
confidence: 96%
“…Uric acid is a by‐product of amino acid metabolism, such as purines, an important structure for DNA (Yu et al, 1998), which may be used to ameliorate oxidative stress (Klandorf et al, 1999). In children, high levels of serum uric acid were associated wither higher triglyceride levels, and the authors discussed that uric acid promotes lipid peroxidation, and may increase blood‐vessel wall inflammation (Baldwin et al, 2011; Chu et al, 2021). Therefore, we suggest that the underlying mechanism for covariation between uric acid and triglyceride concentrations in house finches might also be stress related.…”
Section: Discussionmentioning
confidence: 99%